El lenguaje no verbal en la producción de lenguajes expresivos (2021)
The objective of this research was to analyze how non-verbal language encourages fourth grade students from Colegio Cooperativo San Antonio de Prado in the production of expressive languages during Spanish language classes. Relating to the method, this study was oriented under the qualitative paradigm and a hermeneutical approach; likewise, the techniques used to collect the information were: an unstructured interview, a non-participant observation and a closed survey. With respect to the results, these participants use literature in Spanish language classes as the main vehicle to communicate because of teachers' incentive and concern to improve the reading and writing processes; thus, expressions such as music, theater, dance and drawing are practiced to a lesser extent. In education, more importance is given to verbal language, leaving aside the non-verbal one; as a consequence, teachers limit themselves to making it known in a simple way and without generating awareness of its use. Concerning the discussion and conclusions, verbal language in expressive languages production is a quite good tool for mainstreaming the contents from different areas of knowledge. Therefore, this language is gaining strength in virtuality, inasmuch as students apply it when communicating through their social networks and digital applications.